Adrenal incidentaloma - Acevedo, Carlos; Perrier, José P (Cirugía del Uruguay, 2003)
The suprarenal incidentaloma is the most common suprarenal anomaly in cmTent clinical practice. Its incidence has been increasing dramatically over the last two decades (1 % to 4% of abdominal tomographies detect an incidentaloma) and presents, every time, a challenge to the surgeon when deterrnining therapy: modality: observation or surgery. There follows a discussion of the various pathologies that may appear as suprarenal incidentaloma, contemporary diagnostic methodology and mode of treatment.